2016
DOI: 10.1371/journal.pone.0154662
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prescriptions and Prophylaxis in Italian Children. Is It Time to Change? Data from the ARPEC Project

Abstract: BackgroundAntimicrobials are the most commonly prescribed drugs. Many studies have evaluated antibiotic prescriptions in the paediatric outpatient but few studies describing the real antibiotic consumption in Italian children’s hospitals have been published. Point-prevalence survey (PPS) has been shown to be a simple, feasible and reliable standardized method for antimicrobials surveillance in children and neonates admitted to the hospital. In this paper, we presented data from a PPS on antimicrobial prescript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
45
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 45 publications
14
45
4
Order By: Relevance
“…The patients were treated mostly with ceftriaxone (35.3%), clindamycin (15.7%), vancomycin (11.8%), meropenem (9.8%), and azithromycin (7.8%). This finding is consistent with that found in European countries, which reported LRTI as a common cause of inappropriate antibiotic prescription (6,34). In comparison, the prescription rates were significantly higher for vancomycin and clindamycin and significantly lower for macrolides in our hospitals (6).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The patients were treated mostly with ceftriaxone (35.3%), clindamycin (15.7%), vancomycin (11.8%), meropenem (9.8%), and azithromycin (7.8%). This finding is consistent with that found in European countries, which reported LRTI as a common cause of inappropriate antibiotic prescription (6,34). In comparison, the prescription rates were significantly higher for vancomycin and clindamycin and significantly lower for macrolides in our hospitals (6).…”
Section: Discussionsupporting
confidence: 93%
“…• Judicious use of inflammatory markers such as procalcitonin for differentiation of bacterial and viral diseases (44) • Implementation of annual PPS programs as a useful, simple, and cheap way for quality assessment and finding targets for improvement in hospitals at national levels (6) Our study has several limitations. First, the study could not assess the duration of antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study has shown that 73% of children who seek health care are prescribed antibiotics. Although this is less than over 80% reported by some investigators, it is higher than that observed in some studies, where the antibiotic prescription rates range from 35% to 65% [12][13][14]. [17,18].…”
Section: Discussioncontrasting
confidence: 59%
“…ASPs are commonly focused on in-hospital therapeutic and perioperative prophylactic antimicrobial use [4]. However, up to 90% of antimicrobial use occurs in the outpatient setting, of which, next to family practice, internal medicine and paediatrics are the largest contributors [5,6]. Available studies evaluating outpatient antibiotic use addressed therapeutic antimicrobial use in the ambulatory setting in general, of which 30-50% was inappropriately prescribed [7][8][9].…”
Section: Introductionmentioning
confidence: 99%